Delayed release of a fragrance from novel ionic liquids. (6th January 2017) - Ferrero Vallana, Federico M.; Holland, Lynette A. M.; Seddon, Kenneth R.; Todini, Oreste
Abstract : We present a new technology based on delayed release of perfume raw materials from new-to-the-world binary ionic liquid mixtures. Abstract : When organic molecules are dissolved in ionic liquids (which have no effective vapour pressure), the vapour–liquid equilibria (as measured by infrared spectroscopy of the gas phase) revealed significant deviation from Raoult's law for a wide range of perfume raw materials. Previously, we had demonstrated a positive deviation from Raoult's law, enhancing the vapour pressure of the organic components. Here we developed a designed strategy for the ionic liquids which induces a negative deviation from Raoult's law, hence depressing the vapour pressure of the organic solutes.